Reunion del Comite Directivo del Proyecto de Frijol del CIAT para la Zona Andina PROFRIZA (3, 1990. Quito, Ecuador). Informe (International Center for Tropical Agriculture, 1990)
The new regional subprojects on technology generation and transfer, submitted for approval by the Comite Directivo del Proyecto de Frijol para la Zona Andina (PROFRIZA) in its 3rd meeting, are presented. These include (1) on-farm research on bean cultivation with the participation of farmers (Bolivia); (2) on- farm bean artisanal seed production and management (Ecuador); (3) bean artisanal seed production (Peru); (4) integrated control of bean anthracnose (Ecuador); and (5) technology development for the control of Colletotrichum sp. and Ascochyta sp. in bean crops in the Andean subregion (Peru). For each project, information is provided regarding background, institutional framework, objectives (general and specific), methodology, description of the site, training, plant material, work plan, data recording, budget, and activity schedule, among others. (CIAT)